Efeito da época de semeadura e população de plantas sobre o potencial produtivo e caracteres agronômicos em soja - Luiz, Marlize Cristina Pinheiro (2018)
Soy is one of the main cultivated species in the world with great economic expression and high impact in Brazilian agribusiness. The productive potential is expressed as a function of the genetic makeup of the cultivar and the environment they are exposed to. The market demand for grain production requires the optimal management of the crop to optimize the yield potential of the plant. In this context, crop management is paramount for success in soybean cultivation. The time of sowing and the population of plants exert influence on the agronomic traits and, consequently, in the yield, these factors require particular studies for each crop in Uberlândia, Minas Gerais. The objective of this study was to evaluate the influence of sowing season and plant population on yield potential and agronomic traits in soybean. The experiments were installed at Fazenda Capim Branco, belonging to the Federal University of Uberlândia. The study consisted of 15 treatments in a 3 x 5 factorial scheme, consisting of three cultivars (UFUS 7415, UFUS 7401 and UFUS 6901) and five plant populations (200, 240, 280, 320 and 360 thousand ha-1 plants), in two sowing seasons (October and November 2016). A randomized complete block design was used, with five replications. The evaluated traits were: number of days of flowering and maturity (NDF and NDM), plant height at flowering and maturity (APF and APM), number of nodes at flowering and maturity (NNF and NNM), height of first pod), total pod number (NVT), thousand grain weight (P1000G) and productivity (PROD). It was observed that the plant population did not interfere in the soybean cycle, number of nodes and weight of a thousand grains. The sowing time has an effect on plant height at flowering and maturity, number of total pod and thousand grain weight. In the sowing of October, UFUS 6901, UFUS 7415 and UFUS 7401 showed better yields in the 240, 280 and 320 thousand ha-1 plants respectively, and in November, UFUS 6901 remained with a high production in the population of 240 thousand plants ha-1, UFUS 7415 and UFUS 7401 showed maximum yield in the population of 360 thousand ha-1 plants.